2000
DOI: 10.1074/jbc.275.13.9087
|View full text |Cite
|
Sign up to set email alerts
|

Chlorophyll Binding to Peptide Maquettes Containing a Retention Motif

Abstract: The motif Glu-X-X-His/Asn-X-Arg is conserved in the first and third membrane-spanning domains of all lightharvesting chlorophyll a/b-and a/c-binding proteins in chloroplasts. Molecular modeling of synthetic peptides containing the sequence Glu-Ile-Val-His-Ser-Arg, a motif found in the apoprotein of the major light-harvesting complex in plants, generated a loop structure formed by intrapeptide, electrostatic attraction between Glu and Arg. His, Asn, and charge-compensated Glu-Arg pairs are known ligands of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
52
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 22 publications
1
52
0
Order By: Relevance
“…Interestingly, this domain contains a binding maquette for Chl(ide) similar to that identified by Eggink and Hoober (29). Yamasato et al (30) proposed that this motif may provide a sensor for synthesis of Chl(ide) b in chloroplasts and observed that its deletion drastically affected the stability of the enzyme.…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, this domain contains a binding maquette for Chl(ide) similar to that identified by Eggink and Hoober (29). Yamasato et al (30) proposed that this motif may provide a sensor for synthesis of Chl(ide) b in chloroplasts and observed that its deletion drastically affected the stability of the enzyme.…”
Section: Discussionmentioning
confidence: 97%
“…[94] A recent study demonstrated binding of a water-soluble bacteriochlorophyll derivative to a de novo designed haembinding four-helix bundle. [97] There are also other examples of Chl binding to synthetic peptides, [98][99][100] photo-active pigments such as Ru-pyridines, flavins and light-sensitive porphyrins [47,[101][102][103] (Fig. 2).…”
Section: Modified Bacterioferritin As a Photoactive Reaction Centrementioning
confidence: 99%
“…His or Asn and charge-compensated Glu-Arg pairs are ligands of the Mg atom in chlorophyll. As expected, these retention motifs bind two molecules of chlorophyll (21). Because chlorophyll a binds more readily than chlorophyll b to the motifs, it is suggested that chlorophyll a is bound first and then oxidized to chlorophyll b by chlorophyllide a oxidase (CAO; ref.…”
mentioning
confidence: 99%
“…2 (13,21,22). Structure analysis (23) and site-directed mutagenesis (24) have identified the sequence motifs Glu-X-X-His͞Asn-X-Arg as binding sites of chlorophyll in the first and third membranespanning domains of light-harvesting chlorophyll a͞b and a͞c proteins.…”
mentioning
confidence: 99%